Effect of Ginger and Garlic Supplement on Biochemical Profile and Sensory Meat Quality of Japanese Quail: doi: 10.5958/2581-6616.2021.00005.0 - Murthy, K. Raja Samba; Nath, D. Narendra; K, Naga Raja Kumari.; Kumar, D. Srinivas (Journal of Meat Science, 2022)
A trial was conducted to study the effect of supplementation of ginger, garlic, and their combinations in J. quail diets  on biochemical profile and meat sensory quality. Day-old quail chicks (n=150) were distributed randomly into five  treatments with three replicates containing ten birds each and fed with five experimental diets T1 (Basal diet/BD), T2 (BD+ 1% ginger), T3 (BD+ 2% garlic), T4 (BD+ 0.25% ginger and 0.5% garlic) and T5 (BD+ 0.5% ginger and 1% garlic)  from day one to five weeks of age. Two birds per replicate were slaughtered on day 35th, and meat and blood samples were  collected accordingly. The results revealed that serum total cholesterol and triglyceride values were significantly decreased  in T3 and T5 groups. Serum HDL cholesterol values were significantly (p
Keywords: Ginger; Garlic; Meat quality; Cholesterol; J. Quails